2021
DOI: 10.9734/jeai/2021/v43i630701
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Leaf Extract of Piliostigma Thonningii for Control of Root-Knot Nematode (Meloidogyne javanica) on Eggplant

Abstract: Extracts of Piliostigma thonningii were tested for their effectiveness in controlling Meloidogyne javanica eggs and juveniles in the laboratory and on eggplant cv ‘Yalon Data’. A thousand juveniles were placed in 12 petridishes and extracts of P.  thonningii (Crude extracts, 5 ml dilution and 10 ml dilution of the crude extracts) were dispensed into the petridishes. One thousand eggs of the M. javanica were placed in 12 petridishes and treated with the same extracts used on the juveniles. For the field experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Piliostigma thonningii leaf aqueous extracts were applied by drenching around eggplants in a field that had been infected with M. javanica. The results revealed that the crude extract-treated eggplants had the tallest plants, the most fruits per plant, the highest yield, and the lowest galling indices and final nematode populations [69].…”
Section: Soil Drenchingmentioning
confidence: 98%
“…Piliostigma thonningii leaf aqueous extracts were applied by drenching around eggplants in a field that had been infected with M. javanica. The results revealed that the crude extract-treated eggplants had the tallest plants, the most fruits per plant, the highest yield, and the lowest galling indices and final nematode populations [69].…”
Section: Soil Drenchingmentioning
confidence: 98%
“…Chemicals such as carbofuran and methyl bromide have been used to control RKN (Fatoki, 2001;Adegbite, 2003;Orisajo and Dongo, 2007;Orisajo et al, 2008) but their extreme level of toxicity to man, plants and environmental pollution has precluded them from such use. Attention then turned to the use of plants in the form of powders, extracts and compost to control RKN and they have been found to be effective in reducing the harmful activities of nematodes on crops as well as being nontoxic to man and the environment (Coltro-Roncato et al, 2016;Bajestani et al, 2017;Bakr, 2018;Ogwulumba and Ogwulumba, 2018;Aji et al, 2019;Mamman et al, 2020;Moazezikho et al, 2020;Mamman et al, 2021). This necessitated the use of B. costatum to find out if it has the potential to curb damage to crops by M. javanica.…”
Section: Introductionmentioning
confidence: 99%